"Electron Theory" and the Emergence of Atomic Physics in Japan. Issue 3 (5th September 2018) - Ito, Kenji
Argument: This paper discusses one aspect of the context in which atomic physics developed in Japan between 1905 and 1931. It argues that during this period, there was a social context in which atomic physics was valued as a study of the electron and was thus relevant to electrical engineering. To demonstrate this, I first show that after the Russo-Japanese War, electrical engineering was deemed a valuable and viable field of research in Japan. Second, I show that physicists wrote textbooks and popular accounts about the electron, covering topics from both atomic physics and electrical engineering and presenting the former as relevant to the latter. Finally, as an example of how atomic physics partially emerged from this context, I discuss the group of Kujirai Tsunetarō, an electrical engineer who worked in the physics department of the Institute for Physical and Chemical Research (RIKEN). From Kujirai's group, Nishina Yoshio started his career and became the most important Japanese atomic and nuclear physicist of the 1930s.